IMPROVING MATHEMATICS LEARNING ACTIVITIES USING STUDENT TEAMS ACHIEVEMENT DIVISION OF COOPERATIVE LEARNING MODEL - Siti Karlina; Romelan Hamzah (AdMathEduSt: Jurnal Ilmiah Mahasiswa Pendidikan Matematika, 2021)
The Teacher-centered learning results in students for being less active in responding to the teacher explanations. Therefore, there is a need for efforts to improve students learning activities. This study aims to improve mathematics learning activities using student teams achievement division (STAD) type of cooperative learning. This research was included in the classroom action research consisting of two cycles. The settings in this study were the students of class VII C in the second semester SMP Negeri 1 Imogiri Bantul in the academic year of 2018/2019, with 32 students consisting of 12 male students and 20 female atudents. The research used observation and interviews as the data collection method. The research instrument used in the form of an observation sheet and interview guidelines. The test of the research instrument is the validity test. The researcher used descriptive and qualitative methods to analyzed the datas. The results showed that using using student teams achievement division (STAD) type of cooperative learning model could improve mathematics learning activities of students of class VII C in the second semester of SMP Negeri 1 Imogiri Bantul in thr academic year of 2018/2019. This is evident from the results of observation of mathematics learning activities of student who experience an increase in earch cycle. In the first cycle the percentage of students mathematics learning activities was 40.95% with sufficient criteria. In the second cycle the percentage of students mathematics learning activities was 79.427% with good criteria. From the result of the interview it is obtained information that in general students are interested and feel happy in mathematics learning using student teams achievement division (STAD) type of cooperative learning model.